Intraarterially Administered Verapamil as Adjunct Therapy for Cerebral Vasospasm: Safety and 2-Year Experience - Feng, Lei (AJNR Am J Neuroradiol, 2002)
BACKGROUND AND PURPOSE: Despite the widespread use of angioplasty, adjunct chemical therapy is often needed to treat patients with cerebral vasospasm. In this study, we examined the safety of intraarterial administration of verapamil to patients with cerebral vasospasm. We herein summarize our 2-year experience with this treatment. METHODS: We retrospectively reviewed the procedure reports, anesthesia records, clinical charts, and brain images of 29 patients who received intraarterially administered verapamil in 34 procedures for the treatment of vasospasm after subarachnoid hemorrhage from July 1998 to June 2000. The average changes in mean arterial pressure and heart rate were used to measure cardiovascular side effects. The neurologic effects were assessed by angiographic findings, the results of neurologic examinations performed before and after the procedure, and findings of CT of the head. RESULTS: The average dose of verapamil per patient was 3 ± 0 mg or 44 ± 5 mcg/kg. The average changes in mean arterial pressure at 10 and 20 minutes were −5 ± 1 mm Hg and −2 ± 1 mm Hg or −3.8 ± 1.0% and −1.7 ± 1.1%, respectively. No significant change of heart rate was observed at 10 minutes. The patients showed no sign of increased intracranial pressure by hemodynamic parameters, neurologic examination, or CT of the head. On 10 occasions, when the effect of verapamil infusion was assessed angiographically, there was 44 ± 9% increase of vessel diameter in the spastic segment. Neurologic improvement was noted after five of 17 procedures when verapamil was used as the sole treatment. CONCLUSION: Low dose verapamil is safe when administered intraarterially to patients with cerebral vasospasm. Beneficial effects are achieved in some patients, prompting further study of its efficacy.